Utilisation of modern processing technologies among shea butter processors in Niger State, Nigeria (2018)
The study assessed the level of utilization of modern processing technologies among processors in Niger State, Nigeria. Multi-stage sampling procedure was used to select 217 respondents for this study. Interview schedule was used to collect data which were analysed with descriptive and inferential statistics. Generally, the level of utilization of modern processing technology was low (57.6%). However, milling to fine paste (μ=1.97), use of matured, fresh and un-cracked nuts (μ=1.91), Keep butter in cool and dry place (μ=1.90) and milling machine (μ=1.86) were the most utilized technologies. The respondents identified lack of credit facility (μ=1.72), lack of government assistance (μ=1.68) and high cost of processing equipment (μ=1.67) as constraints to use modern processing technologies. There was significant relationship between respondent’s age (r=0.245, p=0.00), years of experience (r=0.198, p= -0.004), constraints (r=0.152, p= -0.027) and awareness (r=0.792, p= 0.00) with their level of utilization of modern processing technologies. Niger State Commodity Export Promotion council should make effort to increase the number of Shea butter processing villages across the state and extension service in the state needs to be invigorated to adopt Shea programme seriously to be able to reach-out to more processors.